Loop-Mediated Isothermal Amplification of Specific Endoglucanase Gene Sequence for Detection of the Bacterial Wilt Pathogen Ralstonia solanacearum - Lenarcic, Rok; Morisset, Dany; Pirc, Mnaca; Llop, Pablo; Ravnikar, Maja; Dreo, Tanja (PLOS, 2022)
The increased globalization of crops production and processing industries also promotes the side-effects of more rapid and efficient spread of plant pathogens. To prevent the associated economic losses, and particularly those related to bacterial diseases where their management relies on removal of the infected material from production, simple, easy-to-perform, rapid and cost-effective tests are needed. Loop-mediated isothermal amplification (LAMP) assays that target 16S rRNA, fliC and egl genes were compared and evaluated as on-site applications. The assay with the best performance was that targeted to the egl gene, which shows high analytical specificity for diverse strains of the betaproteobacterium Ralstonia solanacearum, including its non-European and non-race 3 biovar 2 strains. The additional melting curve analysis provides confirmation of the test results. According to our extensive assessment, the egl LAMP assay requires minimum sample preparation (a few minutes of boiling) for the identification of pure cultures and ooze from symptomatic material, and it can also be used in a high-throughput format in the laboratory. This provides sensitive and reliable detection of R. solanacearum strains of different phylotypes.